The effects of perceived usefulness and perceived ease of use on acceptance towards office assistance application among employers to disabled employees / Nor Intan Adha Hafit … [et al.] - Hafit, Nor Intan Adha; Othman, Nor Azairiah Fatimah; Rusdi, Syezreen Dalina; Mahpar, Nurul Salizawatee; Mat Sharie, Mohd Fariq Izmeer (Universiti Teknologi Mara Selangor, 2020)
Employment among people with disabilities remains debatable. This paper investigates employers' points of view towards accepting technological assistance for employees with disabilities at the workplace. Specifically, this paper examines the effects of perceived usefulness and perceived ease of use on acceptance towards Office Assistance Application among employers to disabled employees. Acceptance towards any technology has been broadly tested using Davis' Technology Acceptance Model (TAM). To prove if that is the case or not for Office Assistance Applications within the context of employers to employees with disabilities, this research was undertaken to affirm the past research. Data was collected via online questionnaires from 35 employers to Micro Enterprises organization. 6 of surveyed employers were current employers to disabled workers, 18 employers affirmed interest to employ PWDs in the future with 9 employers asserted no interest to hire disabled workers. Data was analysed using Partial Least Square Structural Equation Modelling (PLS-SEM). The result showed two hypotheses were supported evidencing positive and significant relationship between perceived ease of use and perceived usefulness, and relationship between perceived usefulness and technology acceptance. Findings are useful for employers to improve functions of their disabled workers at the workplace along with increasing employment prospects for people with disabilities.